Fire the hired gun: Eliminating expert bias in the accusatorial-adversarial civil justice system - Kehrhahn_FHH, Ferdinand Heinrich Hermann (Department of Public Law, 2025)
In 1954, an expert witness, Dr Unsworth, testifying for the defendant, exculpatorily opined that the plaintiff was a malingerer, but had he testified for the plaintiff instead, his opinion would be that the plaintiff's condition was post-traumatic at the hands of the defendant. 1 This statement captures the essence of the adversarial expert bias problem. As early as 1843, selection expert bias (adversarial bias) was observed in AngloAmerican jurisdictions. 2 From a cursory search of South African case law, more fully set out in section 4.8, it is evident that expert bias is a legitimate and significant problem. 3 This work considers the problematic manifestation of expert bias in South Africa and possible responses thereto in the context of a predominantly adversarial procedural system, but the problem is in no way confined to the adversarial legal systems